2020
DOI: 10.1111/jgs.16846
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Patient‐Reported Frailty and Non‐Home Discharge Among Older Adults Undergoing Surgery

Abstract: BACKGROUND/OBJECTIVES Identifying surgical patients at risk for discharge to a post‐acute facility has the potential to reduce hospital length of stay, improve postoperative planning, and increase patient satisfaction. We sought to examine the association between a positive response to a preoperative patient‐reported frailty screen and non‐home discharge (NHD). DESIGN Prospective cohort. SETTING Urban tertiary academic preoperative evaluation center. PARTICIPANTS Convenience sample of patients aged 60 and olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…We also found that both the SFNR-frailty index and frailty phenotype were predictive for non-home discharge, which is in accordance to prior studies, but in other clinical settings ( 10 , 16 ). In a primary care setting, an electronic frailty index using routine data to identify frailty was predictive for a combined endpoint of mortality, hospitalization and nursing home admission ( 16 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We also found that both the SFNR-frailty index and frailty phenotype were predictive for non-home discharge, which is in accordance to prior studies, but in other clinical settings ( 10 , 16 ). In a primary care setting, an electronic frailty index using routine data to identify frailty was predictive for a combined endpoint of mortality, hospitalization and nursing home admission ( 16 ).…”
Section: Discussionsupporting
confidence: 91%
“…In a primary care setting, an electronic frailty index using routine data to identify frailty was predictive for a combined endpoint of mortality, hospitalization and nursing home admission ( 16 ). Similarly, Sokas et al ( 10 ) reported an association of patient-reported frailty and non-home discharge among older adults undergoing surgery. Our study adds to the literature, that both frailty tools predict non-home discharge in acute care geriatric patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“… 30 Another study found both frail (25.9%) and prefrail (26.9%) participants to have higher odds of a fall compared to nonfrail participants (13.4%). 26 Results for functional outcomes were not pooled due to the heterogeneity of the outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this cohort study3 was to investigate any association between frailty and discharge destination in a convenience sample of older adults, aged 60 and over, undergoing elective major abdominal surgery that was expected to require an acute hospital stay of 3 or more days. Screening for frailty involved completion of four questions from the FRAIL screening tool,4 where participants self-reported their fatigue, weight loss, ambulation ability and activity against resistance (ability to climb stairs).…”
Section: Methodsmentioning
confidence: 99%